Performance characterization and thermal imaging of large scale ground mounted solar photo voltaic plant in Western India - Kasim Ravani; Debasis Sarkar; Indrajit Mukhopadhyay; Tejas Thaker; N. Ranganath (Sustainable Energy Research)
Abstract This paper aims to carry out thermal imaging for the performance characterization of large-scale solar power plants by identifying the hotspots developed in the solar panels and analyzing their effects on overall power generation. A case study of a 1 MW solar power plant in Gandhinagar, Gujarat, India was considered for the study. Polycrystalline and thin-film modules are the primary objects used in the power plant under study. It has been observed that the average arial hotspot density for the polycrystalline module was 0.66/m2, whereas for continuous thin-film module, it was 0.69/m2. It has also been observed that the maximum power generation was about 1371.61 kWh for the polycrystalline module in March 2013 and minimum power generation was 677.35 kWh in August 2022. For the thin-film module, the maximum power generation was 1322.84 kWh in March 2013 and the minimum power generation was 757.387 kWh in August 2013. The maximum performance ratio for the polycrystalline module was 82.73% in March 2022 and the minimum performance ratio was 79% in the month of December 2013. For thin-film module, maximum performance ratio was 95.3% in August 2022 and the minimum performance ratio was 75.73% in the month of August 2013.